MNGI-08. A RARE CASE OF INFANTILE PAPILLARY RHABDOID MENINGIOMA. (5th November 2018) - Bhunia, Nabanita; Mullin, Jeffrey; Carlson, Aimee; Wathen, Connor; Bingaman, William; Tekautz, Tanya
Abstract: Infantile meningioma is exceedingly rare, frequently larger and of higher-grade histology than older patients. We describe a case of papillary meningioma with rhabdoid features in a 6-month-old, previously healthy infant. During evaluation for accidental head trauma the patient was found to have a large heterogeneous mass in the right temporal parietal region with midline shift and uncal herniation on cranial Computed Tomography (CT).Magnetic resonance imaging (MRI) of the brain revealed a large extra axial middle cranial fossa lesion with involvement of sphenoid and extraconal space of right orbit. There was no metastatic disease on MRI spine, CT chest, abdomen and CSF studies. A diagnostic cerebral angiogram showed a hyperplastic right middle meningeal artery (MMA) supplying the tumor. Skull base near total resection of tumor was performed after embolization of the right MMA pedicle artery and right ophthalmic artery recurrent branch. Pathology was consistent with papillary meningioma with focal rhabdoid features. Comprehensive genomic profile was positive for Neurofibromatosis (NF) type II. MRI obtained 4 weeks after initial resection revealed local progression. Gross total resection(GTR) of residual tumor was performed. In view of rapid progression, chemotherapy was initiated 12 weeks from diagnosis, as per Dana Farber Protocol 02-294 for ATRT (Atypical Teratoid Rhabdoid Tumor). Therapy related complications included – febrile neutropenia, Candida rugosa fungemia, loss of vision in right eye and right ear sensorineural hearing loss. The patient continues to be in remission 1 year after completion of his therapy. There are no established guidelines for the management of pediatric rhabdoid meningiomas. Multiagent chemotherapy as per DFCI ATRT 02-294 along with GTR should be considered as a potential treatment option for papillary rhabdoid meningioma. Radiation therapy should be excluded in younger patients due to risk of neuro-cognitive sequelae. Patients with meningioma associated with NF II need to have lifelong follow up.